Xanthones and flavonoids from Leiothrix curvifolia and Leiothrix flavescens - Santos, L. C.; Piacente, S.; De Riccardis, F.; Eletto, A. M.; Pizza, C.; Vilegas, Wagner [UNESP] (Elsevier B.V., 2001)
8-Carboxymethyl-1,6-dihydroxy-3,5-dimethoxyxanthone 8-carboxymethyl-1,5,6-trihydroxy-3-methoxyxanthone and 8-carboxy-methyl-1,3,5,6-tetrahydroxyxanthone were isolated from the capitula of Leiothrix curvifolia and Leiothrix flavescens and characterized by spectroscopic methods, mainly 1D and 2D NMR experiments, as well as by electrospray mass spectrometry. Eight known flavonoids were also isolated and they were identified by 1D and 2D NMR experiments and comparison with literature data. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: xanthone; flavonoids; Leiothrix sp.; Eriocaulaceae